Uncountably many wild knots whose cyclic branched covering are S3 - Montesinos-amilibia, Jose María (Revista Matemática Complutense, 2003)
There is a disk in S3whose interior is PL embedded and whose boundary has a tame Cantor set of locally wild points, such that the n-fold cyclic coverings of S3 branched over the boundary of the disk are all S3: An uncountable set of inequivalent wild knots with these properties is exhibited.